NYXIA UP RISING : THE NYXIA TRIAD - Reintgen, Scott (United Kingdom : Penguin Books, 2019)
The Genesis team finds their escape from the planet cut off after their launch station is destroyed. The countdown is on as the collision of the two moons closes in and the remaining group of Genesis and Adamite survivors attempt to cross battle-strewn continents in an effort to escape Eden in time. The battle will eventually take them to space, where they will wrestle with Babel for control of the only ships that can get them home.
Keywords: Space mining -- Fiction; Interstellar travel -- Fiction; Life on other planets -- Fiction; Survival -- Fiction; Science fiction